2017
DOI: 10.1149/2.0051708jes
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Performance of Anatase TiO2Nanotube Arrays Electrode in Ionic Liquid Based Electrolyte for Lithium Ion Batteries

Abstract: Ternary electrolyte composed of 1-butyl-1-methylpyrrolidinium bis(trifluoromethanesulfonyl)imide ionic liquid (PYR 14 TFSI), γ-butyrolactone (GBL) and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and anatase TiO 2 nanotube arrays (NTAs) electrode are investigated for the application in new generation of lithium-ion batteries (LIBs). The electrical conductivity and viscosity are measured in the whole composition range at several temperatures. Also, cyclic voltammetry experiments are performed at differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 46 publications
3
12
1
Order By: Relevance
“…The four first CVs for the different Nb‐doping concentrations, and for the undoped reference material, are shown in Figure 2. The CV response in the 1 st cycle is similar for the all electrodes and are similar to previous results for anatase [16,18] . The insertion peak in the first cycle is located around −1.3 to −1.4 V (vs Ag/Ag + ) and can thus be related to the two‐phase intercalation region [19] .…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The four first CVs for the different Nb‐doping concentrations, and for the undoped reference material, are shown in Figure 2. The CV response in the 1 st cycle is similar for the all electrodes and are similar to previous results for anatase [16,18] . The insertion peak in the first cycle is located around −1.3 to −1.4 V (vs Ag/Ag + ) and can thus be related to the two‐phase intercalation region [19] .…”
Section: Resultssupporting
confidence: 87%
“…However, an irreversible capacity loss when using common organic electrolytes limits the applicability of TiO 2 [16,17] . To mitigate this problem different electrolyte formulations have been proposed and a promising route is the use of ionic liquid (IL) based electrolytes [18,19] . It has been suggested that the presence of an IL stabilizes the surface of the active material and in this way reduces the irreversible capacity loss.…”
Section: Introductionmentioning
confidence: 99%
“…As continuation of our scientific work [37,38], in this research study are examined the physicochemical and electrochemical properties of 0.5 mol•dm −3 LiTFSI ionic liquid 1,3diethylimidazolium bis(trifluoromethylsulfonyl)imide, C 2 C 2 imTFSI, as well as the performance of anatase Ti/TiO 2 nanotube array (NTA) cells-that electrode material enhances the capacity and energy density of the battery upon lithiumion (Li + ) intercalation and the ability of nanotubes to intercalate/deintercalate Li + large number of times [39]. In order to examine temperature effect on cell performances, cyclic voltammetry (CV) and galvanostatic charge/discharge experiments are performed in a wide temperature range 298.15 to 328.15 K. The electrochemical testing was conducted in order to compare the stability of selected electrolyte with previous one, which contains γ-butyrolactone, GBL, as cosolvent [37], where it is assumed that there is a possibility of stabilization effect between the carbonyl group of GBL and acidic C2-H from 1,3-dialkylimidazolium cation.…”
Section: Introductionmentioning
confidence: 89%
“…Figure 6 a shows that values of the overall capacity of anatase TiO 2 NTAs, which exceeds theoretical capacity, come from the large contribution of lithium surface storage capacity, which does not depend on bulk diffusion time. The relative contribution of surface storage capacity decreases with the temperature increase because of the increased diffusion coefficient of lithium-ion [37,38], but remains significant. The decrease in the difference between voltage plateaus in charge and discharge with the temperature increase shows the expected diminution of overall resistance of the cell at higher temperatures.…”
Section: Voltage Profilesmentioning
confidence: 99%
“…15 By reducing viscosity and altering other physicochemical properties, it was shown that this mixture could be applied as an electrolyte for Li-ion batteries. 21 Therefore, as a continuation of our previous studies toward the understanding and comprehension of the basic properties of (IL + molecular solvent) binary mixtures, the volumetric and transport properties of 1-butyl-1-methylpyrrolidinium bis(trifluoromethylsulfonyl)imide ionic liquid, [bmpyrr][NTf 2 ], with DEC were for the first time investigated in this work. Computational analysis based on both density functional theory (DFT) calculations and molecular dynamics (MD) simulations were performed to achieve an additional insight into the interactions between constituting components of a binary mixture, understanding better the interactions between IL and DEC.…”
Section: Introductionmentioning
confidence: 99%